2016
DOI: 10.1080/03009742.2016.1218543
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in older adults: prevalence, incidence, and risk factors

Abstract: Even though pain was often highly prevalent and persistent, our results show that both recovery and onset of pain occurred. Pain characteristics, rather than age-related symptoms and psychosocial variables, predicted pain persistence among older women but not among older men. These findings highlight the importance of early pain management in the prevention of future pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 21 publications
11
93
0
18
Order By: Relevance
“…Larsson et al demonstrated a correlation between old age and persistent pain, which is similar to our study (42). However, their report showed that PD was more correlated with older females than senior men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Larsson et al demonstrated a correlation between old age and persistent pain, which is similar to our study (42). However, their report showed that PD was more correlated with older females than senior men.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study are in line with our study that showed patients with older age appeared to be at excess risk of chronic pain. Also, the prevalence of chronic or disabling chronic pain was higher in females in both studies (41,42).…”
Section: Discussionmentioning
confidence: 75%
“…This bias may have influenced participants' responses. Thirdly, the level of fidelity of the aging-simulation suit is questionable because this suit did not simulate pain [13,20] and dementia [21,22] whose prevalence increases with aging. Nevertheless, this question regarding fidelity [27] of pedagogical simulation exists whatever the field concerned (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This mixed evidence and current scarcity of previous work highlights the need for additional research to determine under which conditions and for whom intranasal OT may be effective. This combined with evidence that older women are more likely to report experiencing chronic pain (Larsson et al, 2017) calls for future comprehensive investigations of age-by-sex variations in treatment response to intranasal OT administration and its impact on pain management.…”
Section: Age-by-sex Differencesmentioning
confidence: 99%